DMAIC methodology to solder paste printing process in Printed Circuit Boards - Sezgin, Beyza Nur (2017)
Nowadays, production of defective items is a crucial issue for manufacturers. In repetitive and mature processes with low defect levels, measured by defects per million opportunities (DPMO), it is difficult to reduce them even further. The purpose of this study is to reduce the defects rate in one key process, surface mount technology (SMT). The methodology is based on case study of an automotive supplier of electrical and electronic devices. It focuses on implementing Six Sigma tools, using the DMAIC to improve the solder paste printing process of Printed Circuit Boards (PCBs) in SMT. In the case study, solder paste volume defect is defined as the most common type of defect occurred in the process. The used method (proflow) was compared with a new selected method (squeegee) using statistical analyses. The volume defect was reduced over 50% and the sigma level was increased from 5.0 to 5.2.